Normas, Límites y Comunicación Parento- Filial En Familias con un Adolescente que se Autolesiona (2019)
The present investigation is of a qualitative type and its purpose is to analyze the norms, limits and parental filial communication in families with a teenager who self-injures. Allowing to make use of concepts related to the systemic model. To obtain better results in the investigation, a descriptive type scope and a narrative design were considered, using as an instrument the open interview, which was applied to four adolescents between 13 and 18 years. As an important finding, problems were identified that the participants stated that they had regarding the different situations they face day after day, these are of type, family, school and sentimental, which generated emotional distress, where sometimes the feeling of guilt was stronger, given this they went to cutting, as a way to overcome that emotional pain, where they said they prefer to feel the physical pain, since this made them forget their problems.